Cr (VI)-Containing electri furnace dust and filter cake: characteristics, formation, leachability and stabilisation - Garbers-Craig, Andrie Mariana (University of Pretoria, 2013)
Thesis (PhD (Metallurgical Engineering))--University of Pretoria, 2007.